Epidemiology of HIV and AIDS among Adolescents and Young Adults in the United States - Fowler, G. Mary (Journal of Adolescent Health, 2006)
Purpose: To describe the current status of the human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) epidemic among adolescents and young adults in the United States. Despite reported declines in sexual risk behaviors among adolescents in the past decade, little has been published about the epidemiology of HIV and AIDS among adolescents and young adults in the United States. Methods: We analyzed cases of HIV or AIDS diagnosed among persons aged 13 to 24 years and reported to the national HIV/AIDS Reporting System. We used AIDS cases diagnosed from 1985 through 2003 from the 50 states, the District of Columbia, and the U.S. trusts and territories, and we used HIV cases diagnosed in 2003 from 32 states and the U.S. Virgin Islands. We present five-year trends in HIV diagnoses from 1999 through 2003 from 33 surveillance areas that have stable name-based HIV reporting. The data were adjusted for reporting delays and unreported risk factors. Results: At the end of 2003, 7074 adolescents and young adults, aged 13 to 24 years at the time of diagnosis, were living with AIDS in the United States. Of these, 63% were aged 20 to 24 years. AIDS rates were highest among black persons (63 per 100,000) and youth living in the South (22 per 100,000) and Northeast (18 per 100,000). Among females, the number of diagnosed HIV cases decreased from 1611 cases in 1999 to 1454 in 2003. Among males, the number increased significantly from 1763 in 1999 to 2443 in 2003. The observed increase in the number of HIV diagnoses among males was driven by an increase in HIV diagnoses among young men who have sex with men. Conclusions: National case surveillance data for persons aged 13 to 24 years revealed that the burden of HIV and AIDS falls most heavily upon the Southern region of the United States and disproportionately upon black and Hispanic youth. The observed increases in the number of HIV cases among men who have sex with men are congruent with recent reports that suggest a resurgence of HIV among these young men. Our findings highlight the need for intensified HIV prevention efforts within minority communities and among men who have sex with men as well as strengthened efforts to encourage at-risk youth to get tested for HIV. © 2006 Society for Adolescent Medicine. All rights reserved
Keywords: Adolescent; HIV; AIDS; Surveillance